Bounded financial rationality by owners or administrators of mexican micro-enterprises - Palacios-Duarte, Pablo Daniel; Pérez-Paredes, Alfredo; Torralba-Flores, Amado (Cuadernos de Administración, 2019)
The Limited Financial Rationality by Owners or Administrators of Mexican Micro-Enterprises work aims to evaluate the rationality limited per responsible individual subjected to choosing the direction to follow that allows survival in the market. Empirical research is based on a data collection instrument applied to a sample of microenterprises. The main objective is to hierarchically categorize behaviors, ideas and orientations that explain rational construction by owners or managers towards financial decision making. Our contribution is the construction of a behavioral map by micro-entrepreneurs under two financial rationalities, strong and weak, determined by the learning curve (learning by doing). Where the model did prove that limited financial rationality is positively influenced by business maturity explained by the analogy between intuition and the financial situational perception of the microentrepreneur, which is guided by learning, knowledge, risk aversion and is not only defined by the business scale.